Structural characterization and dehydration kinetics of Kirka inderite mineral: Application of non-isothermal models - Figen, Aysel Kantuerk; Yilmaz, Muege San; Piskin, Sabriye (ELSEVIER SCIENCE INC, 2010)
Coats-Redfern, Arrhenius, Ozawa, Kissinger, and Doyle non-isothermal kinetic models were used to calculate the dynamic kinetic parameters for dehydration reaction of Mg-borate mineral, inderite (Kirka - Turkey) based on thermogravimetric analysis, derivative thermogravimetric analysis and differential thermal analysis. Dehydration experiments were carried out at different heating rates of 2, 5, 10, 15, and 20 degrees C/min in a pure nitrogen atmosphere. Structural and morphological properties have been characterized by X-Ray diffraction, Fourier transform-infrared spectroscopy, Scanning electron microscopy-energy dispersive spectroscopy, and Inductively coupled plasma-optical emission spectroscopy techniques. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Inderite; Characterization; Dehydration; Kinetics; Non-isothermal; Thermal analysis; Materials Science; Metallurgy & Metallurgical Engineering